(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2024)
In order to provide quality and effective public services, the government needs to hold public tenders in order to make up its permanent staff. However, in order to meet the temporary need of exceptional public interest, the Constitution admits the temporary hiring of minimally qualified people, subject to simplified selection processes, observing certain formalities and respecting the principles that govern the Public Administration. The analysis of this issue will be the subject of this work, especially with regard to the divergence of case law and the interpretation of the Federal Supreme Court on the parameters of legality, the hypotheses of nullity, as well as the rights arising from these exceptional hirings, as provided for in themes 916 and 551.